(untitled) (Third Sector Social Economic Review, 2023)
The study aims to conduct a comprehensive, holistic analysis of theses on education/training and employment/employability in Turkey from 2000-2021. This study used the descriptive content analysis method of content analysis and the categorical analysis technique; its population contains 55 theses on education/training and employment/employability between 2000-2021, open to access in the National Thesis Center of the Council of Higher Education (CoHE), 55 theses whose sample meets the criteria conducted in Turkey. A Theses Review Form on Education/Training and Employment/Employability was created to collect the data, the data were analyzed by creating summary tables and graphs with Excel, and the categories’ frequencies were given. After evaluating the theses, it was seen the subject was widely studied in state universities’ educational sciences departments after 2011 as master’s theses; sampling regions were not specified, quantitative research method, institutional data sets, and questionnaires were used, the sampling method was not specified, but secondly, the whole universe and accessible sampling methods were preferred, statistical analysis method was mostly not specified, followed by descriptive and inferential statistical analysis and inferential statistical analysis, percentage and frequency were used. As a result, diversifying the sampling area, research method, data collection tools, and analysis in future studies is recommended.